Black Males in Black Churches. Issue 150 (June 2016) - Hodges, Traci L.; Rowland, Michael L.; Paulette Isaac‐Savage, E.
Abstract : The educational role of the Black church is explored along with its role in educating Black males and preparing them for leadership in the community and society.